2000
DOI: 10.1080/000368400322769
|View full text |Cite
|
Sign up to set email alerts
|

Increasing wage dispersion and the changes in relative employment and wages in Mexico's urban informal sector: 1987-1993

Abstract: This study analyses the role of changes in informal/formal relative employment, wage levels and wage inequality in explaining increasing wage dispersion in Mexico during the 1987-1993 period. From 1987 to 1993, the variance of the log of hourly wages for Mexican workers increased by more than 50 per cent. Using data from the Encuesta nacional de empleo urbano we find that this increase in the overall wage dispersion was mainly driven by increasing wage dispersion in the formal sector coupled with a faster grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…For observationally equivalent workers, wage premiums were associated with formal sector jobs in both ElSalvador in 1990 and Peru between 1985 and 1986. In Mexico during 1990, by contrast, the premium was associated with jobs in the informal sector Pagan and Tijerina-Guajardo (2000). found a positive but decreasing wage premium in the Mexican formal sector during 1987-93.This content downloaded from 130.179.16.201 on Wed, 24 Jun 2015 23:42:49 PM All use subject to JSTOR Terms and Conditions…”
mentioning
confidence: 92%
“…For observationally equivalent workers, wage premiums were associated with formal sector jobs in both ElSalvador in 1990 and Peru between 1985 and 1986. In Mexico during 1990, by contrast, the premium was associated with jobs in the informal sector Pagan and Tijerina-Guajardo (2000). found a positive but decreasing wage premium in the Mexican formal sector during 1987-93.This content downloaded from 130.179.16.201 on Wed, 24 Jun 2015 23:42:49 PM All use subject to JSTOR Terms and Conditions…”
mentioning
confidence: 92%
“…The so-called ''dips'' represent sudden changes in the wage-experience profile that result in observing local convexities over some intervals on the support of experience. Pagan and Ullah (1999) has shown that the returns to experience are not entirely concave. Linton and Nielsen (1995) also uncovered the dip in their empirical study on wages.…”
Section: Modelling Wagesmentioning
confidence: 97%
“…In this case, both functional relationships are estimated with each estimate for the covariate indicating the marginal effect on the conditional mean of wages. This is more 193 40.207 appropriate than its non-parametric counterpart wherein derivative estimation methods need to be implemented to ascertain the respective marginal effects of covariates on the dependent variable (Pagan and Ullah, 1999). It is also appropriate for investigating returns to education.…”
Section: Reexamining the Effects Of Schooling And Experience On Wagesmentioning
confidence: 99%
See 1 more Smart Citation
“…For Mexico, Nacional Financiera (2000), Pagán and Tijerina-Guajardo (2000), and Roberts (1989) found that the size of the informal sector fluctuated with the overall health of the macroeconomy; that is, when the economy improved (i.e., growth in GDP), the size of the informal sector decreased, and vice versa.…”
Section: Introductionmentioning
confidence: 97%